Transcriptomic exploration of the Coleopteran wings reveals insight into the evolution of novel structures associated with the beetle elytron. Issue 2 (8th January 2023) - Linz, David M.; Hara, Yuichiro; Deem, Kevin D.; Kuraku, Shigehiro; Hayashi, Shigeo; Tomoyasu, Yoshinori
Abstract: The acquisition of novel traits is central to organismal evolution, yet the molecular mechanisms underlying this process are elusive. The beetle forewings (elytra) are evolutionarily modified to serve as a protective shield, providing a unique opportunity to study these mechanisms. In the past, the orthologs of genes within the wing gene network from Drosophila studies served as the starting point when studying the evolution of elytra (candidate genes). Although effective, candidate gene lists are finite and only explore genes conserved across species. To go beyond candidate genes, we used RNA sequencing and explored the wing transcriptomes of two Coleopteran species, the red flour beetle ( Tribolium castaneum ) and the Japanese stag beetle ( Dorcus hopei ). Our analysis revealed sets of genes enriched in Tribolium elytra (57 genes) and genes unique to the hindwings, which possess more "typical" insect wing morphologies (29 genes). Over a third of the hindwing‐enriched genes were "candidate genes" whose functions were previously analyzed in Tribolium, demonstrating the robustness of our sequencing. Although the overlap was limited, transcriptomic comparison between the beetle species found a common set of genes, including key wing genes, enriched in either elytra or hindwings. Our RNA interference analysis for elytron‐enriched genes in Tribolium uncovered novel genes with roles in forming various aspects of morphology that are unique to elytra, such as pigmentation, hardening, sensory development, and vein formation. Our analyses deepen our understanding of how gene network evolution facilitated the emergence of the elytron, a unique structure critical to the evolutionary success of beetles. Abstract : Transcriptomic comparisons between the forewings (elytra) and hindwings of beetles identified a set of differentially expressed genes. RNA interference (RNAi) for elytron‐enriched genes revealed novel genes with roles in forming various elytron‐unique features. These findings deepen our understanding of how changes in the gene regulatory network facilitate the evolution of novel traits. Research Highlights: Transcriptomic comparisons between the forewings (elytra) and hindwings of two beetle species identified a set of differentially expressed genes. The hindwing transcriptome shows enrichment of many previously identified wing genes, while the elytron transcriptome highlights gene regulatory networks patterning the morphological features shared between the elytron and body wall of beetles. RNA interference for some of the elytron‐enriched genes in Tribolium revealed novel genes with roles in forming various aspects of the morphological features unique to elytra, such as pigmentation, hardening, sensory development, and vein formation.